Student Profile Values in the Novel Si Anak Pelangi and Its Relevance to Indonesian Language Learning - Sumiyati, Sumiyati; Widayati, Mukti; Nurnaningsih, Nurnaningsih (Universitas Cokroaminoto Palopo, 2025)
Globalization, socio-cultural shifts, environmental changes, and work demands are key factors in instilling the Pancasila student profile in students, one of which is through learning literary works such as novels. This study aims to describe the Pancasila student profile values found in the novel Si Anak Pelangi and their relevance to Indonesian language learning in elementary schools. The study uses a qualitative descriptive method, with data in the form of words, dialogues, quotes, and events in the novel that reflect the Pancasila student profile values. Data sources include the novel Si Anak Pelangi and teaching materials documents. Data were collected through reading, listening, note-taking, and document analysis. Data analysis used a sociology of literature approach with dialectical techniques and interactive analysis in three stages: data reduction, data presentation, and drawing conclusions. The results indicate that the values of the Pancasila student profile—faith, devotion to God, noble character, global diversity, independence, mutual cooperation, creativity, and critical thinking—are found in the novel Si Anak Pelangi by Tere Liye. Its relevance to Indonesian language learning in elementary schools is reflected in learning outcomes, teaching materials, and learning objectives.